Assessing the transition risks of environmental regulation in the United States: Revisiting the Porter hypothesis - Stylianou, Ioanna; Christofi, Michael; Karasamani, Isabella; Magidou, Marina (My University, 2025)
The harmful effects of climate change have brought global warming into focus, prompting a growing body of research on its economic impact and the development of targeted climate policies aimed at mitigating these effects and promoting sustainability. Within this context, the main objective of this paper is to investigate whether the presence of transition risk drivers, in particular, the implementation of environmental policies in the United States, initiates risks or fosters green innovation and financial performance. This performance is related to the adjustment process toward a low-carbon economy, widely known as the Porter hypothesis. Using a panel threshold regression model over the period 1990-2020, our results show that market-based climate policies have a heterogeneous effect on the firm's green innovation and financial performance. Specifically, we find an inverted-U-shaped relationship between carbon price and firm outcomes including green innovation and financial performance. These findings have significant implications for practice, as they reveal the mechanism through which climate policies can optimally affect a firm's green innovation activity and financial performance.
Keywords: transition risk drivers; Porter hypothesis; climate policies; first‐mover advantage; green innovation; risk of bankruptcy; survival analysis; threshold regression; transition risk